Efficacy of Xuebijing Combined with Ulinastatin in the Treatment of Traumatic Sepsis and Effects on Inflammatory Factors and Immune Function in Patients - Su, Yuanchao; Zhang, Yunliang; Yuan, Hongsheng; Shen, Chuan (Frontiers in Surgery, 2022)
Objective: To investigate the efficacy of xuebijing combined with ulinastatin in the treatment of traumatic sepsis and analyze the effects on inflammatory factors and immune function of patients. Methods: 182 patients with traumatic sepsis were selected from June 2017 to September 2021 in our hospital. The patients were divided into the control group and the observation group. Patients in both groups were given routine treatments such as initial resuscitation, blood transfusion, monitoring of lactic acid to guide fluid replacement, early control of infection source, selection of appropriate antibiotics, correction of acidosis, treatment of primary disease, prevention of hypothermia and stress ulcer, application of vasoactive drugs, application of glucocorticoid and nutritional support. The control group was treated with Xuebijing injection on the basis of routine treatment, and the observation group was given Xuebijing injection combined with ulinastatin treatment on the basis of routine treatment. The APACHE II score was applied to evaluate the patients before and after treatment, and the routine blood indicators, inflammatory factor indicators, immune function indicators and liver function indicators were tested. Results: After the treatment, the APACHE II score of the observation group was (10.35±3.04) lower than that of the control group (15.93±4.52) (P<0.05). After treatment, the WBC and neutrophils in the observation group (15.19±2.91) and (0.65±0.04) were lower than those in the control group (16.42±3.44) and (0.79±0.05), and the PLT(162.85±43.92) was higher than that in the control group (122.68±36.89) (P<0.05). After treatment, the levels of serum PCT, IL-6, TNF-α in the observation group were (11.38±3.05), (10.74±3.82) and (9.82±2.35) lower than those in the control groups (17.34±3.29), (15.28±4.05) and (13.24±3.06) (P<0.05). After treatment, the levels of CD3+, CD4+, CD8+, CD4+/CD8+ in the observation group were (50.64±4.98), (40.56±4.82), (27.22±3.29), (1.49±0.24) higher than those in the control groups (46.08±4.75), (34.69±4.08), (25.14±3.18), (1.38±0.19) (P<0.05). Conclusion: Xubijing combined with ulinastatin has a good effect in the treatment of patients with traumatic sepsis, which can effectively improve the condition, reduce the body's inflammatory response, and promote the recovery of patients' immune function and liver function.